Tissue Depletion of Olaquindox and Its Six Metabolites in Pigs and Broilers: Identification of a Suitable Marker Residue - Zhang, Heying; Qu, Wei; Ding, Chaoyue; Han, Juncheng; Xie, Shuyu; Liu, Zhenli; Huang, Lingli; Pan, Yuanhu; Yuan, Zonghui (Frontiers in Veterinary Science, 2021)
The depletion profiles of olaquindox and its six major metabolites, including O1 (N1-deoxyolaquindox), O2 (deoxyolaquindox), O3 (2-carboxamide-3-methylquinoxaline-N4-oxide), O4 (2-carboxymethylaminocarbonyl-3-methylquinoxaline-N4-oxide), O5 (2-carboxymethylaminocarbonyl-3-methylquinoxaline), and O6 [3-methyl-quinoxaline-2-carboxylic acid (MQCA)] were studied with a sensitive and accurate HPLC-UV method in pigs and broilers after oral administration of olaquindox at the rate of 50 mg kg−1 feed for 14 consecutive days. Five medicated pigs and six medicated broilers and one control animal for each time point were anesthetized and killed at different time points (6 h and 1, 3, 7, and 14 days for pigs and 6 h and 1, 3, 5, and 7 days for broilers) after ingestion of the medicated feed ceased and samples of muscle, liver, kidney, and fat were collected. The samples were assayed using a liquid chromatographic method. Mean concentrations of O2 (deoxyolaquindox) metabolite residues in all tissues of pigs were higher than other metabolite residues at each time point. MQCA was detected at lower concentrations and eliminated more rapidly than deoxyolaquindox (calculated t1/2 1.78–2.28 days vs. t1/2 2.04–2.46 days). The elimination half-lives of deoxyolaquindox residue in broilers' liver and kidney tissues (t1/2 >4 days) were much longer than those in pigs. Thus, the use of olaquindox in poultry is clearly inappropriate, as significant drug residues will occur without a withdrawal time. The results that deoxyolaquindox occurs at higher concentrations in kidney tissue and is more persistent than other residues in edible tissues of pigs which indicate that deoxyolaquindox is the most relevant marker residue and should be monitored in the routine surveillance of olaquindox-related residues in foods of animal origin.